Mesonephric-like adenocarcinoma of the ovary with co-existent endometriosis: A case report and review of the literature - Kieran Seay; Tracey Akanbi; Bethany Bustamante; Shweta Chaudhary; Gary L. Goldberg (Elsevier, 2020)
Introduction: Mesonephric-like adenocarcinoma (MLA) is a rare malignant gynecologic neoplasm occurring in the uterine corpus and ovary. The morphological and immunohistochemical characteristics of MLA closely resemble that of cervical mesonephric adenocarcinomas, but whether they share a common histogenesis remains unclear. Two main theories for histogenesis of MLAs include the origination of these neoplasms from mesonephric remnants, as is the case for cervical mesonephric adenocarcinoma, versus the differentiation along a mesonephric pathway from Mullerian lesions. Case: A 67-year-old presented after a right salpingo-oophorectomy for a complex ovarian mass revealed a mesonephric-like adenocarcinoma of the ovary and endometriosis. She underwent a total abdominal hysterectomy, pelvic lymphadenectomy, and infra-colic omentectomy, and diagnosed with Stage IA mesonephric-like adenocarcinoma of the ovary. At 18 months post-operatively, the patient developed flank and abdominal pain and was found to have multiple sites of recurrent disease. She was referred to medical oncology for chemotherapy as she was not a candidate for surgical cytoreduction. Discussion: This case demonstrates the aggressive nature of ovarian MLA and the need for a multidisciplinary approach when determining the treatment. In addition, this case provides further evidence to support the theory that at least a subset of MLAs arises from a Mullerian lesion which then differentiates down a mesonephric pathway.